Mahasiswa Driver Ojek Online (Grab) Universitas Halu Oleo - Ersa Trialmawati Trialmawati; Akhmad Marhadi (JURNAL KABANTI: Kerabat Antropologi, 2023)
This study aims to determine why students choose to work as grabbike drivers and find out the obstacles faced by students while being grabbike driver. This study uses the Phenomenological theory by Berger and Luckmann. This research used a snowball sampling method and qualitative approach with data collection techniques used in the research were field techniques (field research) with in-depth interview method (depth interview), and ordinary observation. The result showed that students chose to become grab bike drivers because they saw a pretty good income opportunity and could fulfill their personal needs so that it didnât burden their parents. It does not have complicated requirements and also a flexible work system so that the work can be done anytime and anywhere, then the obstacles faced by students while being a grab bike driver are difficulty dividing time between study and work, social jealousy towards fellow motorcycle taxi drivers, getting fictitious orders, customers who install the pick-up point not according to the location, and the motorcycle used for work sometimes experiences problems or damage.